2021
DOI: 10.1002/pc.26264
|View full text |Cite
|
Sign up to set email alerts
|

MoS2‐decorated talc hybrid for improving the tribological property of Nomex/PTFE fabric composites

Abstract: Producing self‐lubricating fabric composites with excellent wear resistance and long service life is desired for their use in practical application, yet still challenging. Therefore, a novel nanoparticle of talc‐molybdenum sulfide (MoS2) hybrid nanosheets was synthesized via one‐step hydrothermal reaction in this work and incorporated into the Nomex/polytetrafluoroethylene (PTFE) self‐lubricating fabric composites. The spectroscopic and microscopic characterization demonstrated that the talc‐MoS2 nanosheets we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 43 publications
0
6
1
Order By: Relevance
“…[ 91,92 ] However, although the exfoliation of MoS 2 to monolayer was performed for the first time in 1986, [ 93 ] major attention to the material was drawn only after the emergence of graphene. [ 94–99 ] As soon as Geim and Novoselov's [ 100 ] discussion on the “electric field effect in atomically thin carbon films” gained momentum, several researchers devoted their attention to MoS 2 and other TMDs.…”
Section: Dm Intrinsic Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 91,92 ] However, although the exfoliation of MoS 2 to monolayer was performed for the first time in 1986, [ 93 ] major attention to the material was drawn only after the emergence of graphene. [ 94–99 ] As soon as Geim and Novoselov's [ 100 ] discussion on the “electric field effect in atomically thin carbon films” gained momentum, several researchers devoted their attention to MoS 2 and other TMDs.…”
Section: Dm Intrinsic Propertiesmentioning
confidence: 99%
“…[91,92] However, although the exfoliation of MoS 2 to monolayer was performed for the first time in 1986, [93] major attention to the material was drawn only after the emergence of graphene. [94][95][96][97][98][99] As soon as Geim and Novoselov's [100] discussion on the T A B L E 3 Thermal conductivity of the addressed 2DM and some derivatives…”
Section: Molybdenum Disulfidementioning
confidence: 99%
“…[10][11][12][13] In recent years, polytetrafluoroethylene (PTFE)/ Nomex fabric-reinforced composites (PNFRCs) have been used as self-lubricating liners for spherical plain bearings. 14,15 It is made up of PTFE for lubrication, amide fiber for load capacity, and adhesive resin to combine fine fiber together. 16 To enhance the lubricating property and wear resistance, researchers have conducted extensive research.…”
Section: Introductionmentioning
confidence: 99%
“…Cui et al [5] studied the tribological properties of spherical plain bearings with Nomex/PTFE fabric in a nitrogen environment at −160 °C and found that the transfer film formed on the outer surface of the bearing's inner ring was the main factor leading to the low-temperature lubrication performance. Although the tribological properties of hybrid-fabric composites have been well investigated under ambientand high-temperature conditions [23][24][25][26], there is little research on the tribological properties of PTFEbased fabric composites at cryogenic temperatures; in particular, the mechanism of transfer film formation at cryogenic temperatures remains basically unknown [2,5].…”
Section: Introductionmentioning
confidence: 99%